Short-Term Efficacy of Laparoscopic Treatment for Colorectal Cancer in Patients with Schistosomiasis Japonica - Zhu Yi; Jiang Hong-Gang; Chen Zhi-Heng; Lu Bo-Hao (Gastroenterology Research and Practice)
Introduction. Schistosomiasis is associated with numerous complications such as thrombocytopenia, liver cirrhosis, portal hypertension, and colitis. To the best of our knowledge, the feasibility and outcomes of laparoscopic colorectal surgery in patients with schistosomiasis have not yet been studied. Methods. In this study, the data of 280 patients with colorectal carcinoma along with schistosomiasis japonica infection who underwent laparoscopic or open colorectal surgery were retrospectively analyzed. Preoperative data, operative data, pathological outcomes, postoperative complications, and recovery were compared between patients in the laparoscopic (LAC) and open (OC) groups. Results. There were no significant differences in the preoperative data between the groups. However, fewer postoperative complications, especially severe hypoproteinemia, early postoperative feeding, and shorter postoperative hospital stay, were observed in patients in the LAC group (P<0.001). The mean operative time was higher in the LAC group (180 min versus 158 min; P<0.001), while the mean blood loss was similar (95 mL versus 108 mL; P=0.196) between groups. The mean number of lymph nodes harvested was also similar in both groups (15 versus 16; P=0.133). Conclusion. Laparoscopic surgery for colorectal cancer is safe in patients with schistosomiasis japonica and has better short-term outcomes than open surgery.